Peran Posyantek (Pos Pelayanan Teknologi Tepat Guna) Dalam Pemberdayaan Masyarakat(Studi Deskriptif Kualitatif Peran Komunikasi Posyantek Tekno Mitra Giri dalam Pemberdayaan Kelompok Usaha Kecil di Kecamatan Wonogiri) - Arofah, Dwi Hapsari Nur, Drs. Joko Sutarso, S.E, M.Si (2017)
The society empowerment is being the important aspect that should be cared by the government to assist the nation development process. It is aimportant change by society in order to change the economic, social, and life welfare. The empowerment needs parties to support the improvement process in society. The appropriate technology service post (POSYANTEK) is a organization in sub-district level with function to provide technical, information, promotion and orientation services on appropriate technology. This research uses descriptive qualitative approach, it describes phenomenon factually, systematically and accurately, it is supported by the real facts. This research wants to describe the appropriate technology service post (POSYANTEK) process in society empowerment effort through appropriate technology understanding and using. Data analysis uses analytical technique of Miles and Huberman model, its steps are information collection, data reduction, presentation and final conclusion. These results indicate that communication strategies Posyantek done quite successfully, namely the direct approach and form a group which is visible from enthusiastic people who get the socialization program. Oponion village elections as leaders by Posyantek, provide convenience for empowering to get into the social environment.